Police Anthropology as an Interdisciplinary Framework for Reforming Lemdiklat Polri: Bridging Cultural Gaps in Indonesia’s Multicultural Policing Context - Benyamin Lufpi; Poppy Setiawati Nurisnaeny (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Police education in Indonesia is largely based on legalistic and managerial paradigms that almost completely ignore sociocultural aspects. While no single mechanism accounts for this misleading tendency, such bias nonetheless continues to distort supposedly reforming policies that stray far from field realities particularly in multicultural societies where police-community interactions carry cultural dimensions that exceed mere contextual differences. Objective: This study analyzes the contribution of police anthropology to strengthening the curriculum and learning models that Lemdiklat Polri produces toward integrative model implementation. Methods: A qualitative, interpretive literature review of Polri policy documents, semi-structured interviews (8 key informants), and critical discourse analysis were employed in this study. Thematic analysis was performed to identify themes related to curriculum challenges and sociocultural aspects. Results: The findings showed that the current course content is largely grounded in law and procedure, resulting in officers with technical competence but lacking knowledge of cultural norms, intercultural communication skills, or adequate negotiation techniques. The study subsequently developed an integrative framework MIAP-POLRI to incorporate police anthropology (emic perspectives, participatory ethnography, and culturally grounded learning methods) as a core component of the proposed training model. Conclusion: Police anthropology has the potential to elevate police education, and therefore professionalism, operational effectiveness, and public trust. A shift from procedural compliance-based policing to a fully community-centered and human-centered practice contributes to theory building while generating pragmatic policy recommendations for redesigning the training program for the Indonesian police.